2012
DOI: 10.3113/fai.2012.0336
|View full text |Cite
|
Sign up to set email alerts
|

Snapping of the Extensor Digitorum Longus Due to Attenuated Inferior Extensor Retinaculum: Case Report

Abstract: For information on pricings and availability of reprints, email reprints@datatrace.com or call 410-494-4994, x232.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In children, traumatic avulsion of the SER may cause a subperiosteal hematoma; US has been demonstrated as an imaging modality to depict it . Extensor digitorum longus tendon intermittent subluxation due to IER loosening is also described, although rare . In addition to being a retaining aponeurosis, studies have demonstrated the role of the IER in stabilizing the subtalar joint; therefore, its injuries may be implicated in subtalar instability (Figure ) …”
Section: Extensor Retinaculamentioning
confidence: 99%
“…In children, traumatic avulsion of the SER may cause a subperiosteal hematoma; US has been demonstrated as an imaging modality to depict it . Extensor digitorum longus tendon intermittent subluxation due to IER loosening is also described, although rare . In addition to being a retaining aponeurosis, studies have demonstrated the role of the IER in stabilizing the subtalar joint; therefore, its injuries may be implicated in subtalar instability (Figure ) …”
Section: Extensor Retinaculamentioning
confidence: 99%
“…8 Anterior ankle snapping syndrome is rare. Snapping of the extensor digitorum longus due to attenuated inferior extensor retinaculum 9 and snapping due to hypertrophied or low-lying peroneal tertius muscle 10,11 have been reported. Snapping can also be due to impingement of ankle tendons with bone spurs, osteophytes, fracture fragments, or orthopaedic hardware.…”
mentioning
confidence: 99%